Understanding Tourist Visiting Decisions Through Viral Marketing, E-Wom, And Destination Image Perspectives - Lestariawati, Diyah; Hawa, Sarah Dien (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the influence of viral marketing and electronic word of mouth on visiting decisions with destination image as an intervening variable at Goa Lawa Purbalingga tourism destination. The background of this study is based on the fluctuation in the number of tourist visits to Goa Lawa Purbalingga, which indicates the dynamics of tourists’ visiting decisions. This study employed a quantitative approach using a survey method by distributing questionnaires to 190 respondents. The data analysis technique used Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results showed that viral marketing (X1) had no effect on visiting decisions (Y). Meanwhile, electronic word of mouth (X2) and destination image (M) had a positive and significant effect on visiting decisions (Y). Viral marketing (X1) and electronic word of mouth (X2) also had a positive and significant effect on destination image (M). In addition, destination image (M) was able to mediate the influence of viral marketing (X1) and electronic word of mouth (X2) on visiting decisions (Y). These findings indicate that tourism managers need to focus more on strengthening destination image and improving tourist experiences in order to encourage visiting decisions.